A Study on Students’ Learning Inte rest in Blended Learning Method Through Edmodo to the Students of English Department at Nusantara PGRI Kediri University - Rika Riwayatiningsih (STKIP PGRI TULUNGAGUNG, 2015)
Over the past few years, technology has grown to influence nearly every aspect of the education system.The development of Information technology has generated new environments called blended learning which combine the advantages of e- learning and traditional learning. Edmodo is one of the blended learning mediums which has been used for teaching at English Department of Nusantara PGRI Kediri University. The purpose of the present study was to examine the students’ learning styles and their views on blended learning. This study is a qualitative descriptive research which data collection was done by interviewing the lecturer, distributing questionnaires and interviewingthe students. Additional data were gathered from achievement scores of students; and records demonstrate students’ participation to–learning environment. Results revealed that students have an interest in blended learning method through Edmodo both in the individual interest and situational interest also ease of using of the web environment, evaluation, face to face environment etc., differ according to their learning styles. Results also reveal on responds to face to face aspect of the Edmodo are available for iPhone and Android, the students can know the right answer of the assignment directly, it helps the extrovert students who are not active in class become more confident, the interface looks like facebook, the students can get the information and new materials more fast. Process when students’ evaluation concerning the implementation is taken to consideration. The overall findings showed no significant differences between students’ achievement level according to their learning styles